Análisis de la percepción respecto al reporte de los eventos adversos y la seguridad del paciente en una IPS de alta complejidad de la ciudad de Medellín (2011)
A risk, in care and patient care may result in the appearance of an adverse event. This type of error is usually the responsibility not only of the person who is a service agent, but of a complex web of human failings, technological and/or processes. Thus, the multidimensionality comprising an adverse event cannot only respond to isolated and circumstantial actions, so in order to avoid this a culture of patient safety in health institutions is necessary. Following this approach, arises the interest and the contribution of this research project which investigated the medical and paramedical staff of IPS, the third level of complexity in the city of Medellin, on the human, institutional and legal factors involved in the reporting of adverse events and knowledge of the culture of patient safety through their beliefs, attitudes and knowledge on this issue